1.2% Rosuvastatin and 1.2% Atorvastatin Gel Local Drug Delivery and Redelivery in the Treatment of Class II Furcation Defects: A Randomized Controlled Clinical Trial. Issue 3 (1st March 2017) - Garg, Shruti; Pradeep, A.R.
Abstract : Background: Statins are one of the lipid‐lowering drugs that help in reducing cholesterol levels in the body by specifically inhibiting 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase, which is a rate‐limiting enzyme for cholesterol synthesis. Rosuvastatin (RSV) and atorvastatin (ATV) have shown bone stimulatory and anti‐inflammatory effects. The present study aims to explore efficacy of 1.2% RSV and 1.2% ATV gels as a local drug delivery and redelivery system adjunct to scaling and root planing (SRP) for treatment of Class II furcation defects. Methods: Ninety patients with mandibular buccal Class II furcation defects were randomly allocated to three treatment groups: 1) SRP with placebo gel (group 1); 2) SRP with 1.2% RSV gel (group 2); and 3) SRP with 1.2% ATV gel (group 3). Clinical and radiographic parameters were recorded at baseline and after 6 months. Gels were redelivered at the respective sites at a 6‐month recall appointment. All clinical and radiographic parameters were recorded again after 3 months (i.e., 9 months from baseline). Results: Greater mean probing depth (PD) reduction and greater mean gain in relative vertical clinical attachment level (CAL) and relative horizontal CAL were seen in the RSV group than in the ATV group at 6 and 9 months. Significantly greater mean percentage of defect depth reduction (DDR) was found in the RSV group (30.80% ± 8.35%, 41.86% ± 6.76%) than in the ATV group (25.54% ± 8.89%, 34.31% ± 8.04%) at 6 and 9 months, respectively. Conclusion: The RSV group shows significant improvement in all clinical parameters and significantly greater DDR compared with the ATV group in treatment of mandibular Class II furcation defects as an adjunct to SRP.